Integralitas Sistem Sanad dan Kontekstualisasi Pemahaman Hadis Versus Konsep Sunah Muh?ammad Shah?rûr - Amrulloh Amrulloh (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2017)
This article discusses the concept of Sunna promoted by Muh?ammad Shah?rûr, one of the most controversial contemporary Islamic scholars of Syrian Islamic thought, as well as his critical study. Here the author attempts to expose the unappreciative attitude of Shah?rûr to the existence of the sanad system which is an integral part of the construction of the criticism of the Hadith. In fact, at the same time, he made the Hadith as the basis for the inference of the maximum limits of a law in its boundary theory. By describing, analyzing and then criticizing the views of the Shah?rûr on the concept of the Sunna, the authors came to the conclusion that the Shah?rûr lawsuit against the existence of the Hadith Sciences and its lack of appreciation of the sanad system is not necessary.